Inclusive education in English language teaching: strategies, challenges and prospects - Jumaniyazova, Lobar; Shukurova, Shohsanam (The Lingua Spectrum, 2025)
This article investigates the integration of inclusive education principles into English Language Teaching (ELT) in Uzbekistan. It emphasizes that inclusive ELT is not only about providing access for learners with disabilities but also about creating flexible, learner-centered environments where all students—regardless of their background or needs—can succeed. The study relies on a qualitative review of international reports, national education policies, and classroom case studies from 2015 to 2025. Special focus is given to the Universal Design for Learning (UDL) framework, which promotes multiple means of representation, engagement, and expression. The results show that inclusive strategies such as differentiated instruction, assistive technologies, and teacher training significantly enhance academic participation and outcomes for students with special educational needs (SEN). However, challenges persist, including limited resources, infrastructure gaps, and low awareness among educators. The article concludes with strategic recommendations for expanding inclusive ELT through curriculum reform, professional development, and international cooperation—positioning inclusion as a key component of quality education and national development.